Application of Clustering Method to Explore the Correlation Between Dominant Flora and the Autism Spectrum Disorder Clinical Phenotype in Chinese Children - Chen, Biyuan; You, Na; Pan, Bangquan; He, Xueyi; Zou, Xiaobing (Frontiers in Neuroscience, 2021)
Autism spectrum disorder (ASD) is characterized by deficits in social interactions and repetitive, stereotypic behaviors. Evidence shows that bidirectional communication of the gut-brain axis plays an important role. Here, we recruited 62 patients with ASD southern China, and performed a cross-sectional study to test the relationship between repeated behavior, gut microbiome composition, and alpha diversity. We divided all participants into two groups based on the clustering results on their microbial compositions and found Veillonella and Ruminococcusas the seed genera in each group. Repetitive behavior differed between clusters, and cluster 2 had milder repetitive symptoms than cluster 1. Alpha diversity between clusters was significantly different, indicating that cluster 1 had lower alpha diversity and more severe repetitive, stereotypic behaviors. Repetitive behavior had a negative correlation with alpha diversity. We demonstrated that the difference in intestinal microbiome composition and altered alpha diversity can be associated with autism repetitive, stereotypic behavior. The role of Ruminococcus and Veillonella in ASD is not yet understood.